Dynamic Effects of Raw Materials Price Shocks for Large Oil-Dependent Economies - Hans-Werner Wohltmann; Roland C. Winkler (Kiel University, Department of Economics, 2005)
The paper analyzes the dynamic effects of anticipated price increases of imported raw materials upon two large open economies. It is assumed that the economies have an asymmetric macroeconomic structure on the supply side and are dependent upon a small third country for oil or raw materials imports. The dynamic behavior of several macroeconomic variables is discussed under alternative scenarios. We first assume that oil is priced in dollars. Thereafter, we investigate the impacts of oil price shocks on the domestic and the foreign economy if oil imports are denominated in terms of domestic currency (Euro) rather than US dollars. It is shown that with domestic- currency denominated oil the stagflationary effects of oil price increases upon both the domestic and foreign economy are reduced. The paper also discusses several monetary policy responses to oil price shocks.
Keywords: Q43; F41; E63; 330; oil price shocks; international policy coordination; time inconsistency; currency denomination; Mineralölpreisschock; Zwei-Länder-Modell; Konjunkturzusammenhang; Zeitkonsistenz; Internationale wirtschaftspolitische Koordination; Währungsumrechnung; Makroökonomischer Einfluss; Theorie